2021
DOI: 10.1017/s0033291721002361
|View full text |Cite
|
Sign up to set email alerts
|

Mental health impact of the COVID-19 pandemic in U.S. military veterans: a population-based, prospective cohort study

Abstract: Background: The coronavirus disease-2019 (COVID-19) pandemic has caused myriad health, social, and economic stressors. To date, however, no known study has examined changes in mental health during the pandemic in the U.S. military veteran population. Methods: Data were analyzed from the 2019-2020 National Health and Resilience in Veterans Study, a nationally representative, prospective cohort survey of 3,078 veterans. Pre-to-peri-pandemic changes in psychiatric symptoms were evaluated, as well as pre-pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 75 publications
7
61
1
2
Order By: Relevance
“…Older veterans indicated that the pandemic increased loneliness and sorrow due to the isolation and disruption of their ordinary routines [ 13 ], and researchers also found that a lack of social support and increasing numbers of pandemic-related stressors were associated with mental health difficulties [ 14 ]. In a national sample of US veterans, the pre- to peripandemic prevalence of generalized anxiety disorder increased from 7.1% to 9.4%, with the most pronounced increase observed in veterans aged 45-64 years (8.2% to 13.5%) [ 15 ]. Results of this study further indicated that prepandemic loneliness and pandemic-related social stressors were associated with an increase in psychological distress [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older veterans indicated that the pandemic increased loneliness and sorrow due to the isolation and disruption of their ordinary routines [ 13 ], and researchers also found that a lack of social support and increasing numbers of pandemic-related stressors were associated with mental health difficulties [ 14 ]. In a national sample of US veterans, the pre- to peripandemic prevalence of generalized anxiety disorder increased from 7.1% to 9.4%, with the most pronounced increase observed in veterans aged 45-64 years (8.2% to 13.5%) [ 15 ]. Results of this study further indicated that prepandemic loneliness and pandemic-related social stressors were associated with an increase in psychological distress [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a national sample of US veterans, the pre- to peripandemic prevalence of generalized anxiety disorder increased from 7.1% to 9.4%, with the most pronounced increase observed in veterans aged 45-64 years (8.2% to 13.5%) [ 15 ]. Results of this study further indicated that prepandemic loneliness and pandemic-related social stressors were associated with an increase in psychological distress [ 15 ]. Although suicide among veterans over the course of the pandemic did not increase, low social support and worsening of social relationships were among the risk factors present for veterans who did develop new-onset suicide ideation during the pandemic [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for this finding could be that loneliness is associated with painful emotions (e.g., sadness, jealousy; OliĂ© & Courtet, 2020), whereas the social connectedness measures reflect more disparate aspects of social support that are less reflective of perceived quality of social relationships and perceptions of social isolation and belongingness. Taken together, these findings suggest that loneliness may potentially have greater prognostic utility in predicting suicide attempts than previously conceptualized and thus warrants additional attention in future research, particularly in light of recent research from the COVID‐19 pandemic, which has demonstrated increasing rates of loneliness (Groarke et al, 2020; Hill et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…The findings of this study are consistent with emerging results regarding the mental health of veteran populations during the pandemic. In a nationally representative sample of US military veterans, the prevalence of major depressive disorder and PTSD positive screens remained stable while the prevalence of generalized anxiety disorder positive screens increased [ 10 ] and the rate of suicidal ideation decreased nearly 10 months into the pandemic [ 9 ]. Regarding the mental health among treatment-seeking veterans with pre-existing mental health difficulties, the UK study revealed no significant changes in symptoms of PTSD during the pandemic [ 11 ] and a study conducted in Croatia revealed a decrease in PTSD symptoms during the onset of the pandemic as compared to the measurement a year before [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the veteran population, the results from recent studies revealed resilience to mental health problems and lower rates of suicidal ideation among US military veterans nearly 10 months into the pandemic [ 8 , 9 ]. However, these studies also showed that the prevalence of generalized anxiety disorder increased and the prevalence of major depressive disorder and post-traumatic stress disorder (PTSD) remained stable during the pandemic [ 10 ]. A recent longitudinal study, conducted during the period between two lockdowns among treatment-seeking veterans with pre-existing mental health difficulties in the UK, did not find any significant changes in symptoms of PTSD, common mental health disorders, anger, or alcohol use between the lockdowns [ 11 ].…”
Section: Introductionmentioning
confidence: 99%